2018
DOI: 10.3390/nu10040497
|View full text |Cite
|
Sign up to set email alerts
|

Meeting Vitamin D Requirements in White Caucasians at UK Latitudes: Providing a Choice

Abstract: The body gains vitamin D through both oral intake (diet/supplementation) and synthesis in skin upon exposure to ultraviolet radiation (UVR). Sun exposure is the major source for most people even though sun exposure is complex and limited by climate and culture. We aimed to quantify the sun exposure required to meet vitamin D targets year-round and determine whether this can be safely achieved in a simply defined manner in the UK as an alternative to increasing vitamin D oral intake. Data from observation (sun … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 26 publications
0
66
1
Order By: Relevance
“…Recent work has started to define the amount of sun exposure required to maintain a sufficient vitamin D status in HLC and it is feasible and realistic for paler skinned urban dwellers to attain this. For example in the UK, Webb [48] estimated that 9 minutes per day between March and September, exposing the forearms, lower legs, hands and face (from June to August) and just the hands and face (March to May, September) was enough to keep individuals above 25nmol/L all year around. However, for South Asians, who typically have skin type V, a longer time period was required (24-40 minutes, with 35% of skin exposed to the sun), which is likely to be less feasible to achieve [49].…”
Section: Time Spent Outdoorsmentioning
confidence: 99%
“…Recent work has started to define the amount of sun exposure required to maintain a sufficient vitamin D status in HLC and it is feasible and realistic for paler skinned urban dwellers to attain this. For example in the UK, Webb [48] estimated that 9 minutes per day between March and September, exposing the forearms, lower legs, hands and face (from June to August) and just the hands and face (March to May, September) was enough to keep individuals above 25nmol/L all year around. However, for South Asians, who typically have skin type V, a longer time period was required (24-40 minutes, with 35% of skin exposed to the sun), which is likely to be less feasible to achieve [49].…”
Section: Time Spent Outdoorsmentioning
confidence: 99%
“…For this work, we considered a 25(OH)D concentration <25 nmol/L as deficient (following SACN, [4]) and <50 nmol/L as insufficient (following the IOM and EFSA, [9,10]). Using the same definitions, data modelling research reveals that it is theoretically possible to avoid vitamin D deficiency year-round in the UK without incurring skin erythema (a proxy for heightened risk of skin cancer) at least for the white Caucasian population [11,12]. At middle to high latitudes, a seasonal cycle in circulating 25(OH)D was observed, lagging slightly behind the seasonal cycle in solar elevation [13]; consequently, avoiding deficiency throughout winter required higher levels of 25(OH)D to be attained by the end of summer.…”
Section: Introductionmentioning
confidence: 99%
“…58 Based on this rule, Terushkin et al 59 tried to estimate through a computer model, the sun exposure time needed to achieve serum vitamin D 3 concentrations equivalent to 400 or 1000 IU vitamin D for individuals of various skin types and living at different latitudes during different months, but concluded that it is difficult, if not impossible, to titrate one's exposure. More recently, Webb et al 60 showed that, in specified conditions, white Caucasians across the UK need 9 min of daily sunlight at lunchtime from March to September for 25-OH-D levels to remain ≥25 nmol/L throughout the winter.…”
Section: Sunbeds Are Carcinogenic To Humansmentioning
confidence: 99%